REASONS TO REDEFINE MORAL DISTRESS: A FEMINIST EMPIRICAL BIOETHICS ANALYSIS - Morley, Georgina (Bioethics, 2020)
There has been increasing debate in recent years about the conceptualization of moral distress. Broadly speaking, two groups of scholars have emerged: those who agree with Jameton’s ‘narrow definition’ that focuses on constraint and those who argue that Jameton’s definition is insufficient and needs to be broadened. Using feminist empirical bioethics, we interviewed critical care nurses in the United Kingdom about their experiences and conceptualizations of moral distress. We provide our broader definition of moral distress and examples of data that both challenge and support our conceptualization. We pre‐empt and overcome three key challenges that could be levelled at our account and argue that there are good reasons to adopt our broader definition of moral distress when exploring prevalence of, and management strategies for, moral distress.